Experimental evolution under varying sex ratio and nutrient availability modulates male mating success in Drosophila melanogaster. (1st June 2022) - Sepil, Irem; Perry, Jennifer C.; Dore, Alice; Chapman, Tracey; Wigby, Stuart
Abstract : Biased population sex ratios can alter optimal male mating strategies, and allocation to reproductive traits depends on nutrient availability. However, there is little information on how nutrition interacts with sex ratio to influence the evolution of pre-copulatory and post-copulatory traits separately. To address this omission, we test how male mating success and reproductive investment evolve under varying sex ratios and adult diet in Drosophila melanogaster, using experimental evolution. We found that sex ratio and nutrient availability interacted to determine male pre-copulatory performance. Males from female-biased populations were slow to mate when they evolved under protein restriction. By contrast, we found direct and non-interacting effects of sex ratio and nutrient availability on post-copulatory success. Males that evolved under protein restriction were relatively poor at suppressing female remating. Males that evolved under equal sex ratios fathered more offspring and were better at supressing female remating, relative to males from male-biased or female-biased populations. These results support the idea that sex ratios and nutrition interact to determine the evolution of pre-copulatory mating traits, but independently influence the evolution of post-copulatory traits.